2015
DOI: 10.1111/bcp.12752
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of changes in oral drug absorption in preterm and term neonates for Biopharmaceutics Classification System (BCS) class I and II compounds

Abstract: AIMSEvidence suggests that the rate of oral drug absorption changes during early childhood. Yet, respective clinical implications are currently unclear, particularly for preterm neonates. The objective of this study was to evaluate changes in oral drug absorption after birth for different Biopharmaceutics Classification System (BCS) class I and II compounds to better understand respective implications for paediatric pharmacotherapy. METHODSTwo paradigm compounds were selected for BCS class I (paracetamol (acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Thus, lyophilization did not affect drug release from the 1:1 beeswaxtheobroma oil SLN composite matrix and drug release is likely to remain identical between the fresh and lyophilized formulations following administration. The lower release rate of AMB and SSZ from the SLNs is consistent with the fact that AMB [32] and SSZ [33] are class IV drugs (low aqueous solubility and low membrane permeability) according to the biopharmaceutics classification system, whereas PAR is assigned to class I [34] due to its high aqueous solubility and high membrane permeability. The drug release data show that most of the PAR is likely to be released from the SLNs in aqueous/biological media, whereas there is likely to be significant retention of AMB and SSZ within the SLNs prior to absorption after administration.…”
Section: In Vitro Drug Release Studiessupporting
confidence: 79%
“…Thus, lyophilization did not affect drug release from the 1:1 beeswaxtheobroma oil SLN composite matrix and drug release is likely to remain identical between the fresh and lyophilized formulations following administration. The lower release rate of AMB and SSZ from the SLNs is consistent with the fact that AMB [32] and SSZ [33] are class IV drugs (low aqueous solubility and low membrane permeability) according to the biopharmaceutics classification system, whereas PAR is assigned to class I [34] due to its high aqueous solubility and high membrane permeability. The drug release data show that most of the PAR is likely to be released from the SLNs in aqueous/biological media, whereas there is likely to be significant retention of AMB and SSZ within the SLNs prior to absorption after administration.…”
Section: In Vitro Drug Release Studiessupporting
confidence: 79%
“…Based on clinical literature data of selected compounds after iv and oral dosing, Somani et al performed a population PK analysis to evaluate changes in oral drug absorption postnatally. They concluded that the maturational changes in oral drug absorption occur within the first week after birth and are drug-independent (Somani et al, 2016). Besides drug administration by oral route, also nonenteral routes might be used.…”
Section: Neonatal Pharmacology: Driven By Maturational and Nonmaturatmentioning
confidence: 99%
“…This is further exacerbated in preterm neonates, where issues around swallowing and ADME (absorption, distribution, metabolism, and excretion) factors may be less well understood. Clinical evidence suggests, that the oral absorption process of a drug undergoes substantial changes after birth [35,36]. The impact of these physiological changes on oral drug therapy is currently unclear.…”
Section: Formulation Considerationsmentioning
confidence: 99%
“…Clinical examples of differences in absorption in neonates compared to adults are scarce. Recent work suggested that the processes underlying changes in oral drug absorption rate typically reach adult levels within one week of birth [35].…”
Section: Formulation Considerationsmentioning
confidence: 99%